Kajian Arsitektur Islami Pada Masjid-Masjid di Kecamatan Banda Sakti Kota Lhokseumawe - Intan Annisa; Armelia Dafrina; Yenny Novianti; Diana Khairani Sofyan (Jurnal Serambi Engineering, 2023)
The emergence of mosque architecture in Indonesia is inseparable from the development of Islam entering Indonesia. The development of Islamic civilization at all times has produced many forms and types of mosques, so that in Indonesia the forms of mosques are very diverse, especially in Aceh, the city of Lhokseumawe. The existence of Islam in Aceh is proven by the many historical mosques with Islamic architecture that have survived to this day, but in fact the function of mosques is more than that, mosques also act as centers of education, spread of Islamic symbols, and become centers of community empowerment. This research process combines field research (field research) and library research, namely using a qualitative descriptive research form. The mosque building itself is synonymous with Islamic architecture, which has seven important elements including gardens, courtyards, domes, pointed arches, muqarnas, minarets and mihrab, while not all elements of Islamic architecture are found in every mosque building.